Synthesis and performance of AM/SSS/THDAB as clay hydration dispersion inhibitor - Du,Wei-Chao (2019)
Abstract In this paper, a novel zwitterionic copolymer AM/SSS/THDAB clay hydration dispersion inhibitor was synthesized by copolymerization of tris hydroxyethyl diallyl ammonium bromide (THDAB), sodium p-styrene sulfonate (SSS) and acrylamide (AM) initiated in an aqueous solution. The copolymer was characterized by FT-IR, GPC, TGA-DSC and SEM. Results demonstrated that molecular weight of AM/SSS/THDAB was 43674 g/mol and its temperature resistance ability was up to 225 °C. Evaluation experiments showed that AM/SSS/THDAB has an excellent clay hydration inhibitive performance. Methods including particle size analysis and SEM were utilized to study its dispersion inhibition mechanism by using sodium montmorillonite (Na-MMT). Results indicated that the micro-structure of Na-MMT has been successfully changed by AM/SSS/THDAB. In a word, the superior inhibition property makes the novel clay hydration dispersion inhibitor promised in water-based drilling fluids.